Small-Essentially Quasi-Dedekind R-Modules - Shahad, Haithab A.; Al-Muthafar, Nuhad S. (Iraqi Journal of Science, 2022)
In this research, we introduce a small essentially quasi−Dedekind R-module to generalize the term of an essentially quasi.−Dedekind R-module. We also give some of the basic properties and a number of examples that illustrate these properties.